MEASURES TO ENSURE LIQUIDITY AND PRICE STABILITY IN THE CAPITAL MARKET - Muxamedjanov Elmurod Xasanovich (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2026)
This article analyzes measures to ensure liquidity and price stability in capital markets based on empirical evidence from Uzbekistan and international experience covering 2020-2024.